VD_FINDINFO HC / 2009 / 415 vom 10. September 2009 - VD Tribunal cantonal (2009)
USUREDROIT PÉNAL, FIXATION DE LA PEINE, DOMMAGE | 42 al. 2 CO, 157 ch. 1 CP, 47 CP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 415 CPP